Redesign Interior Museum Kesehatan Dr. Adhyatma, MPH di Surabaya - Prayoga, Ivan; Yong, Sherly de; Basuki, Lucky (Intra, 2019)
Dr. Adhyatma, MPH Museum of Health were chosen as design object based on the fact that from year to year Indonesians eagerness to visit museum are decreasing with significant numbers. Dr. Adhyatma, MPH Museum of Health actually provides complete information along with the objects and research reports that have been carried out, and also the object displayed are classified as unique and peculiar, so it can increase the interest of the community to visit the museum, but in fact there are very few visitors. Design thinking used as design method, assisted by questionnaires system to obtain valid data in order to specify the existing problems. Design thinking have 3 main stages, understand; explore; and materialize. Understand, collecting information and specify problems in the design object; explore, experimenting to create a concept that can solve the problems; and materialize, process of introducing design to the community to get a direct feedback. â€œHistoricalâ€ is a concept that solve the problems mentioned before, this concept itself is a combination of 4 words, history, storytelling, interactive, and mimical. This concept is applied through a variety of designs, such as ceilingâ€™s shape and structuring system of museum objects that resemble Rod of Asclepius, which is a medical symbol; and application of technology (Augmented reality and virtual reality) as a conveyor of information (Storytelling).